1987
DOI: 10.1515/zna-1987-0816
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Liquid Structure of Dimethyl Sulfoxide by the X-Ray Diffraction

Abstract: The liquid structure of dim ethyl sulfoxide (DMSO) was investigated by X-ray diffraction. The intramolecular structure parameters were obtained as follows: S = 0 150(1) pm, C -S 180(1) pm, nonbonding C -0 267(4) pm and C ---C 271 (7) pm. It is suggested that the molecular arrange ment in the liquid state is sim ilar to that in the solid state. It is pointed out that not only the value but also the position of the dipole mom ent vector in the molecule is essential for dipoledipole interm olecular interactions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 16 publications
5
29
0
1
Order By: Relevance
“…The Sc-O bond distance 2.069(3) Å in the crystal structure of hexakis(dimethyl sulfoxide)scandium(III) iodide is very close to the Sc-O bond distance 2.068(6) Å for the major component (86% occupancy) of the recently published disordered crystal structure of [Sc(OSMe 2 complex, is probably the reason why the scandium(III) solvation number is lower in dimethyl sulfoxide than in aqueous solution. Raman spectroscopy of 1 mol dm −3 alkali halide solutions in dimethyl sulfoxide has shown that interactions between iodide ions and the methyl groups give rise to a CH 3 asymmetric stretching frequency component at about 2975-2980 cm −1 (in deuterated dimethyl sulfoxide 2238 cm −1 ), downshifted about 15 cm −1 from the band in neat dimethyl sulfoxide.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…The Sc-O bond distance 2.069(3) Å in the crystal structure of hexakis(dimethyl sulfoxide)scandium(III) iodide is very close to the Sc-O bond distance 2.068(6) Å for the major component (86% occupancy) of the recently published disordered crystal structure of [Sc(OSMe 2 complex, is probably the reason why the scandium(III) solvation number is lower in dimethyl sulfoxide than in aqueous solution. Raman spectroscopy of 1 mol dm −3 alkali halide solutions in dimethyl sulfoxide has shown that interactions between iodide ions and the methyl groups give rise to a CH 3 asymmetric stretching frequency component at about 2975-2980 cm −1 (in deuterated dimethyl sulfoxide 2238 cm −1 ), downshifted about 15 cm −1 from the band in neat dimethyl sulfoxide.…”
supporting
confidence: 67%
“…the character and strength of the metal-ligand bond, the internal electron displacement due to the M-O r-bonding and backbonding from metal d-orbitals. This is one reason why a relationship only considering S-O stretching frequencies and bond lengths, as the one published recently by Calligaris (that also includes doubtful assignments for Pd(NO 2 )(pyi)(dmso-O) and (HgCl 2 ) 3 (dmso-O) 2 ), 1 shows a rather diffuse correlation.…”
Section: Interactions In Dimethyl Sulfoxidementioning
confidence: 96%
“…The solvent system was equilibrated by a 250-ps MD run. The radial distribution functions (rdfs) for all of the intermolecular atom pairs, calculated from the atomic trajectories during the last 40 ps MD were found to be in agreement with both Rao and Singh simulations [17] and the X-ray structure of DMSO [18].…”
Section: Computational Proceduressupporting
confidence: 69%
“…10,11,19 The theoretical reduced intensities for intermolecular interactions, iinter(s), are obtained from Eq. (3) and intermolecular structure parameters are refined by the least-squares method to minimize u:…”
Section: Principle For the Determination Of Molecular Orientationmentioning
confidence: 99%
“…Determinations of the local structure of organic liquids such as benzene, formamide, dimethyl sulfoxide, and N-methylacetamide at ambient temperature (their melting points are 5.493, 2.55, 18.55, and 30.55˚C, respectively) are successful examples based on the partial structure in the crystal. [9][10][11][12] In order to obtain further information on the longer range intermolecular interactions of molecular liquids, Iijima and Nishikawa proposed the reciprocal space expansion in the analysis of X-ray scattering data. 13,14 However, these procedures do not apply if the temperature of a liquid is far from its melting point because of large differences of densities between solids and liquids.…”
Section: Introductionmentioning
confidence: 99%